2020
DOI: 10.1183/23120541.00334-2019
|View full text |Cite
|
Sign up to set email alerts
|

SAS Care 1: sleep-disordered breathing in acute stroke and transient ischaemic attack – prevalence, evolution and association with functional outcome at 3 months, a prospective observational polysomnography study

Abstract: Sleep-disordered breathing (SDB) is frequent in patients with acute stroke. Little is known, however about the evolution of SDB after stroke. Most of our knowledge stems from smaller cohort studies applying limited cardiopulmonary sleep recordings or from cross-sectional data collected in different populations.This study aims to determine prevalence, type and intra-individual evolution of SDB based on full-night polysomnography (PSG) in acute stroke and 3 months thereafter. Furthermore, we aimed to identify pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 53 publications
2
21
2
Order By: Relevance
“…These data were further confirmed by a meta-analysis conducted by Hasan et al who evaluated the dynamic prevalence of sleep disorders after stroke or TIA [1 ••]. Recently, the SAS Care 1 study [35] evaluated longitudinally the progression of SDB in a large cohort patient with ischemic stroke or TIA by means of PSG: the authors observed a significant reduction of AHI (baseline: 21 events/h; at 3 months: 18 events/h) driven by a reduction of both the obstructive and central component. Nevertheless, the prevalence of SBD was similar at baseline (85.6%) and at 3 months (82.7%), and a reduction was observed exclusively for severe SBD (AHI > 30/h) and for CSA.…”
Section: Sleep Apnea In Stroke Patients: New Onset or Pre-existing Co...mentioning
confidence: 71%
See 2 more Smart Citations
“…These data were further confirmed by a meta-analysis conducted by Hasan et al who evaluated the dynamic prevalence of sleep disorders after stroke or TIA [1 ••]. Recently, the SAS Care 1 study [35] evaluated longitudinally the progression of SDB in a large cohort patient with ischemic stroke or TIA by means of PSG: the authors observed a significant reduction of AHI (baseline: 21 events/h; at 3 months: 18 events/h) driven by a reduction of both the obstructive and central component. Nevertheless, the prevalence of SBD was similar at baseline (85.6%) and at 3 months (82.7%), and a reduction was observed exclusively for severe SBD (AHI > 30/h) and for CSA.…”
Section: Sleep Apnea In Stroke Patients: New Onset or Pre-existing Co...mentioning
confidence: 71%
“…In a recent meta-analysis performed by Seiler et al [2] conducted on 86 studies for a total of 7096 patients, the prevalence of SA in patients with acute stroke or TIA ranged between 30% (with an AHI > 30/h, consistent with severe SDB) up to 71% (with an AHI > 5/h, consistent with mild SDB); only a slightly lower prevalence was observed in the chronic phase. However, most of the studies included in the meta-analysis evaluated the acute phase, while only few studies [32][33][34][35][36][37] evaluated the intra-individual evolution from acute to the chronic phase. Moreover, few studies [33][34][35][36]38] evaluated the evolution of SDB in stroke by means of polysomnography (PSG), the standard diagnostic test for SDB in stroke patients [39], reporting an improvement, but not a resolution, from acute to sub-acute/chronic phase, of the SDB.…”
Section: Sleep Apnea In Stroke Patients: New Onset or Pre-existing Co...mentioning
confidence: 99%
See 1 more Smart Citation
“…Feasibility of the trial at each centre was evaluated based on the number of admitted stroke patients to a centre, availability of required infrastructure and qualified staff in the necessary disciplines to conduct the trial: neurology, pulmonary medicine and/or sleep medicine as well as neuroradiology. Feasibility of diagnosing and treating SDB in acute stroke patients was shown in former clinical studies of the Bernese study team (SAS CARE 1 & 2, [ 23 25 ]).…”
Section: Methodsmentioning
confidence: 99%
“…Stroke incidence in OSA-positive patients Results from three cohort studies reported by Dae Lim Koo (2018) [3] H. Lee Lau et al (2019) estimate a relative risk of independent association between SAS and stroke of 2.5 in a meta-analysis of 10 cohort studies [4] Sherma (2016) analysing the Sleep Heart Health Study and Wisconsin studies gives the respective results: HZ =2.86 and RR = 4.48 (ci: 1.31 -15.33) [5] Prevalence of OSA in stroke/TIA The results of a meta-analysis and systematic review of 89 studies involving 7,096 patients by Andreas Seiler (2019) are as follows: for AHI >5 events/hour, the prevalence is 71% of patients, for AHI>30 events/hour, the prevalence is 30% of patients [6]. The observational polysomnographic study by Sebastian R. Ott (2020) gives a prevalence of 80.5% for an AHI > 5 events/hour and 25.4% for an AHI > 30 events/hour [7].…”
Section: Epidemiologymentioning
confidence: 99%